The predictive role of composite inflammatory ratio parameters in the conscious awareness recovery after severe acute ischemic stroke: a retrospective cohort study - Yiyuan Xu; Yanyan Liu (BMC Neurology)
Abstract Background Inflammatory mechanisms play a significant role in ischemic stroke. Peripheral neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), systemic immune-inflammation index (SII), systemic inflammation response index (SIRI), which are indicators capable of reflecting the magnitude of the inflammatory response, have been research hotspots. However, few research findings evaluate the prediction significance of these biomarkers in the recovery of conscious awareness following severe acute ischemic stroke. Methods This was a retrospective cohort study of 142 patients with consciousness disorders after acute ischemic stroke (GCS score ≤ 8) treated from January 2022 to May 2024. The cases were divided into three groups according to the GCS score at discharge as died/ vegetative state (GCS ≤ 3),moderate/ severe coma(GCS = 4–11) and mild coma/ normal (GCS:12–15). Demographic and clinical assessment data were reviewed and abstracted. NLR, PLR, SII and SIRI were calculated based on the peripheral blood tests at admission. The study investigated the correlation between changes in GCS scores from admission to discharge (calculated as the GCS score at discharge minus the baseline GCS score, where a negative value indicates worsening and a positive value indicates improvement) and the levels of NLR, PLR, SII, and SIRI. Results The level of NLR, PLR, SII and SIRI in died/ vegetative state group were significantly higher than those in moderate/ severe coma group (p = 0.0429, p = 0.0215, p = 0.0288, p = 0.026, respectively) and mild coma/ normal group (p = 0.0085, p = 0.0079, p = 0.0019, p = 0.0017, respectively). The area under the curve (AUC) values of NLR, PLR, SII, and SIRI to prognosis were 0.670, 0.661, 0.677, and 0.609, respectively. Spearman correlation analysis indicated NLR, PLR and SII were negatively correlated with GCS scores increase during hospitalization (r =- 0.317, p<0.0001 for NLR, r = -0.285, p = 0.001 for PLR, r = -0.3331, p < 0.0001 for SII, r= -0.199,p = 0.018 for SIRI).However, ordinal logistic regression analyses failed to indicate that NLR, PLR, SII and SIRI were independent predictors of poor consciousness response for severe acute ischemic stroke coma patients after adjusting for other confounders. Conclusion Patients with poorer consciousness outcomes exhibited a tendency towards elevated NLR, PLR, SII, and SIRI levels which were inversely correlated with GCS scores increase during hospitalization. However, the four indexes did not exhibit sufficient promise to be the valuable predictors for the prognosis of recovery from consciousness following severe acute ischemic stroke.